Flood impact on urban roads and commuting: A case study of Wuhan, China - Liu, Yaolin; Zhang, Hongxin; Chen, Huiting; Chen, Cuizhen (Frontiers in Environmental Science, 2022)
Rainfall events have become more frequent and more serious, leading to rampant floods. Floods in urban area would greatly impair the serviceability of the transport system and cause disruption to commuting. However, little is know about the commute response under various rainfall scenarios in developing country cities despite the uncertainty of climate change. A high-resolution flood modelling module and commute simulation module were integrated to examine the impact on commuting under floods. Flood maps under three rainfall scenarios with increasing rainfall intensity and duration were obtained, and road vulnerability was assessed considering the speed drop. We innovatively employed Location-based service big data to do the commute simulation under floods based on the shortest time cost principle. Results show that a large amount of passable but affected commuters become disconnected commuters as rainfall intensity increases. And commute loss of each traffic zone would not increase linearly, which means the emphasis and strategy of disaster prevention and mitigation are not the same in different rainfall scenarios. We integrated hotspots of flood exposure , road vulnerability and commuting loss and found that there were inconsistent spatial distribution between three indicators. It indicates that areas need to take different measures according to the local damage characteristics. This paper studied the relationship between severe weather conditions and commuting activity performance at the city level, and has important practical guiding significance for building resilient cities.